Haplotype Analysis of the GL7/GW7/SLG7 Gene and Its Application in Improving the Grain Quality of Three-Line Hybrid Rice - Duo Xia; Peizhou Xu; Shuqin Zheng; Le Xue; Yuejiao Yin; Zhuchen Yao; Sikai Ding; Yusen Lai; Yipei Wang; Xiaoding Ma; Xianjun Wu; Hao Zhou (Rice)
Abstract Improving grain quality is second only to enhancing grain yield in breeding hybrid rice. Yet, rice grain quality, especially milling and appearance quality, is facing increasing threats from global warming due to climate change, leading to a relatively slow progress in high-quality rice breeding. Identifying additional grain quality genes is an effective way to combat against the threats on rice grain quality. In the present study, we used the germplasm from 3,000 Rice Genomes Project for genome-wide association study, and identified GL7/GW7/SLG7 as a major QTL besides GS3 and GW5 for grain shape. Among nine haplotypes of GL7 (H1-9), H1-H4, which harbored an 11-bp deletion, were designated as the functional GL7 allele and were primarily present in Geng/Japonica (GJ) rice. We developed KASP markers for GL7 major haplotypes (H1 and H2), and established a breeding system assisted by the markers to effectively improve Xian/Indica (XI) hybrids for grain quality. Yuehesimiao (YHSM) and Yixiang 1 A (YX1A) are widely applicated XI restorer line and sterile line in three-line hybrids. The improved hybrid YX1A GL7 /YHSM GL7 exhibited longer grain, higher ratio of grain length-to-width and larger rate of head rice, but lower chalkiness rate and degree than that of any other hybrids and both parents. Furthermore, the improved hybrid with GL7 had statistically same yield of grains with all other hybrids, indicating no penalty of grain yield while improving grain quality. The GL7 haplotype along with its marker KASP-S2 and breeding strategy resulted from this study could be valuable sources for developing XI hybrids with high quality and high yield of grains in rice.